The barriers and facilitators to the telephonic application of the FAST assessment for stroke in a private emergency dispatch centre in South Africa - Mackay, Ethan (Afr J Emerg Med, 2021)
BACKGROUND: Stroke is one of the leading contributors to morbidity and mortality globally. The incidence of stroke is on the increase in Sub-Saharan countries such as South Africa. As stroke is a time-sensitive condition, emergency medical services (EMS) play an important role in the early recognition of stroke. The telephonic application of the FAST (Face, Arm, Speech, Time) assessment has been suggested to screen patients for stroke, but this is not applied consistently. This study aimed to identify the barriers and facilitators to the telephonic application of the FAST assessment. METHODS: This retrospective, exploratory study sampled 20 randomly selected emergency calls to a private EMS in South Africa, with suspected stroke. After verbatim self-transcription, data were analysed using inductive content analysis to identify the barriers and facilitators to the application of the FAST assessment. Results were arranged according to themes. RESULTS: Results indicated that in 15/20 (75%) of the calls, the FAST assessment was successfully applied. Eight barriers under three themes (practical barriers, emotionality, and knowledge and understanding) and three facilitators under one theme (clear communication) were identified. Most notably, language discordance, lack of empathy and caller frustration featured prominently as barriers while caller cooperation and clear instructions were prominent facilitators. CONCLUSION: With the barriers known, methods to address these may be constructed. Additional training and credentialing for call-takers may be a reasonable first step. These lessons can likely be applied to other telephonic acuity and recognition algorithms.